Differences in the effects of exercise on blood pressure depending on the physical condition of the subject and the type of exercise: a systematic review and meta-analysis - Suematsu, Yasunori; Morita, Hidetaka; Abe, Makiko; Uehara, Yoshinari; Koyoshi, Rie; Fujimi, Kanta; Ideishi, Akihito; Takata, Kohei; Kato, Yuta; Hirata, Tetsuo; Yahiro, Eiji; Morito, Natsumi; et al. (Hypertension research, 2025)
Although hypertension is a major cause of cardiovascular disease, the control of blood pressure (BP) is insufficient worldwide. Exercise is an effective treatment for reducing BP, but the differences in the blood pressure lowering effects of exercise according to the underlying pathophysiological condition, the type of exercise, and the geographic region are not fully understood. An umbrella review with a meta-analysis of 435 randomized controlled trials that investigated the BP-lowering effects of exercise was performed using Ovid MEDLINE and the Cochrane Library, covering the period from inception to August 1, 2023. A random effects model meta-analysis was performed to estimate the effect size across multiple studies. Exercise significantly reduced systolic BP in healthy subjects (−3.51 mmHg, 95% confidence interval: −3.90, −3.11; p < 0.001) and in those with lifestyle-related diseases including hypertension (−5.48 mmHg, −6.51, −4.45; p < 0.001), but not in those with cardiovascular diseases (−1.16 mmHg, −4.08, 1.76; p = 0.44). According to the type of exercise, all types significantly reduced systolic BP in healthy subjects and in those with lifestyle-related diseases, but not in those with cardiovascular diseases. According to the region, in Oceania, there were no reductions in systolic BP. In Asia, systolic BP was reduced in patients with cardiovascular diseases. In conclusion, any type of exercise reduced BP in healthy subjects and in those with lifestyle-related diseases, but not in those with cardiovascular diseases, and the region affected the effect of exercise. When using exercise to reduce hypertension, it is important to consider the patient’s pathophysiological condition and the region.